The effect of various position of cilcular hollow section on the strength of foamed concrete beam with processed spent bleaching as partial replacement of cement - Afidatul Husna, Mohamad Syariff (2018)
Nowadays construction industry focus in using green material which one of it is processed spent bleaching earth (PSBE) as pozzolan material which offer more pozzolanic reaction. Other than that, application of foamed concrete in construction getting wider from time to time as it able to have high self-compacting and self-flowing. The focus of this research is to study the effect of different location of circular hollow section on the flexural strength of foamed concrete beam containing processed spent bleaching earth as partial replacement of cement. The objectives of this research is to determine the maximum load of the flexural beam, the deflection of flexural beams and the mode of failure of the flexural beam by using four point bending test. By using 30% PSBE as partial replacement of cement, three beam sized 150mm x 200mm x 1500mm casted with 50mm circular hollow section were placed at different height and one controlbeam with the same size. Four point bending test were carried out to obtain the ultimate load and Linear Variable Displacement Transducer (LVDT) were used to measure the deflection. The crack pattern was observed and analyzed. The experimental result shows that Beam 2 produced greater maximum load with 3.320kN, flexural strength with 0.664 N/mm2 and deflection with 0.330mm. The loss percentage of flexural strength increased as the depth of hollow section increased which are 28%, 40.79% and 49.13% for Beam 2, Beam 3 and Beam 4 respectively when compared to Beam 1. The decrement of deflection compared to Beam 1 are 5.71%, 11.43% and 34.0% for Beam 2, Beam 3 and Beam 4 respectively. First crack on the beam was reflected as the ultimate crack since the beam were unreinforced. Hence, the flexural strength and deflection depend on the second moment of inertia which then second moment of inertia depends on the neutral axis. In short, the beam with hollow section at the neutral axis is the suitable beam for future planning of construction due to higher ultimate load and deflection.by adding the reinforcement in any beam application, will be better because the ultimate load and deflection value will be bigger.